Analysis the Industrial Sector Labor and the Small and Medium Enterprises’ Labor on the Two Sectors Economy in East Java - Febry Wijayanti; Sasongko Sasongko; Putu Mahardika (e-2477-1929)
Two-sectors model from Lewis Theory describes the movement of labor who move from agricultural sector to the industrial sector with the assumption that they are moving because the pull of wages. The theory does not consider that the wage problem in the industry sector create movement to the informal sector. This research has two purposes, first, to know the implementation of the industrial sector labor with five variables (GDP growth in the agricultural and industrial sectors, the regional minimum wage rates, labor force and total labor agriculture). Second, the implementation of the small and medium enterprises (SME) labor with five variables (GDP growth in the agricultural and industrial sectors, labor force, agriculture sector labor and industrial sector labor). This research is using quantitative methods with panel regression. Results from this study indicate that the transformation of agricultural labor to industries in East Java, especially the links between agricultural growth and wages on employment in the industrial sector has not been proven. The Lewis theoretical proven is the growth of the industrial sector and the number of workers to the industrial sector employment. There is no correlation between the output agricultural sector and industrial sector of the SME sector. SME sector only be a last resort, after all the labors are rejected from the formal sector.Keywords:Lewis Theory, Agriculture Sector, Industry Sector, SME Sector, Labor and Minimum Wage